Implementation of the Balanced Scorecard as a measuring tool for company performance ( Case Study at PT. ARS Maju Sentosa) - Abdurrachman, Abdurrachman; Bryan Givan, Bryan Givan; Rizky Amalia, Rizky Amalia; Ninuk Riesmiyantiningtias, Ninuk Riesmiyantiningtias; Alan Budi Kusuma, Alan Budi Kusuma; Syah Putra, Arman (CV. Inara, 2022)
The background of this research is how to implement a balanced scorecard to calculate performance in a company. With the opportunity score k method, it can be seen whether the company can develop or not or what things can affect a company that will develop. The method used in this study is to use the literature review method, and use trials on existing data in the company, with this data it can be seen that the real results of the company can progress and develop. The problem raised in this research is how to find out what things can improve the performance of all companies. Therefore, with the balanced scorecard method, it will be known what things are the weaknesses and strengths of a company that will develop so that it can corrected early. the purpose of this research is how to find out the application of the balanced scorecard hood score to work performance in a company so that it can be known what things can affect and be influenced by a company so that things can be fixed that are the shortcomings of a company.